Moderating Environmental Uncertainty on The Effect of Accounting Knowledge and Accounting Information Systems on the Performance of SMES - Robiur Rahmat Putra; Siti Holisoh Lilis (International Journal on Social Science, Economics and Art, 2022)
The purpose of this research is to analyze the influence of accounting expertise and accounting information systems on the performance of MSMEs using environmental uncertainty as a moderating variable.  The research method used is quantitative with data collection techniques through questionnaires. A total of 97 respondents were collected from various MSMEs in the Lagoa sub-district, Jakarta, Indonesia. The sample was tested for validity and reliability as well as hypothesis testing through the Smart PLS software application. The findings indicated that accounting expertise had no discernible influence on MSMEs' performance. Accounting information systems have a substantial impact on the performance of micro, small, and medium-sized enterprises (MSMEs). Uncertainty in the environment might mitigate the influence of accounting expertise on the performance of MSMEs. Environmental uncertainty may mitigate the influence of accounting information systems on the performance of small and medium-sized businesses.